THE CANCELLATION OF GRANT DEED BY THE SIBLING OF GRANT RECIPIENT THROUGH THE COURT’S STIPULATION (A study on Stipulation Number: 581/Pdt.P/2015/PN.SBY) - Deny Muria Hindrato; Hari Purwadi (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2018)
AbstractThis article was written to analyze the judge’s rationale in stipulating the grant deed cancellation by sibling through the Court’s Stipulation Number: 581/Pdt.P/2015/PN.SBY and the legal consequence of grant deed cancellation by the sibling for the beneficiaries of died grant recipient. This law research employed a normative research method with statute and conceptual approaches. The result showed that there are some things inconsistent with the legal provision, including the legal position of sibling as the applicant for deed cancelation was weak, viewed from article 1666 of KUH Perdata (Civil Code), the witness was inconsistent with the provision of Article 145 HIR as he had blood kinship and others’ interest likely harmed in this case, former wife of grant recipient regarding mutual property obtained during marriage. The legal consequence of grant deed against the grant property object for the beneficiaries when the grant recipients had passed away was that the property object was returned to the grant giver. The beneficiaries of grant recipient would have a part of the object as long as the right had not been transferred and when the grant giver passed away.Keywords: Deed Cancellation, grant, court’s stipulation AbstrakArtikel ini disusun untuk menganalisis Tentang Tinjauan Yuridis Pembatalan Akta Hibah oleh saudara kandung penerima hibah melalui Penetapan Pengadilan(Studi Penetapan Nomor : 581/Pdt.P/2015/Pn.Sby).Penulisan hukum ini menggunakan metode penelitian normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Penelitian ini untuk menganalisa dasar pertimbangan hakim dalam menetapkan pembatalan akta hibah oleh saudara kandung dan akibat hukum pembatalan akta hibah bagi ahli waris penerima hibah yang meninggal dunia.Hasil penelitianmenunjukkan ada hal-hal yang tidak sesuai ketentuan hukum, antara lain kedudukan hukum saudara kandung sebagai pemohon pembatalan akta adalah lemah ditinjau dari pasal 1666 KUH Perdata, saksi yang tidak sesuai ketentuan pasal 145 HIR karena memiliki hubungan keluarga sedarah dankepentingan pihak lain yang dapat dirugikan dalam hal ini adalah mantan isteri penerima hibah, Akibat hukum pembatalan akta hibah terhadap obyek harta hibah bagi ahli waris ketika penerima hibah meninggal dunia maka obyek harta tersebut kembali menjadi milik pemberihibah. Ahli waris penerima hibah baru dapat memiliki hak bagian atas obyek tersebut selama obyek hibah belum beralih haknya dan pemberi hibah meninggal dunia.Kata kunci: Pembatalan Akta; hibah;penetapan pengadilan